Suitability of different supported Ru, Pt and Ni catalysts for the hydrogenolysis of sorbitol - Kandasamy, Thirunavukkarasu; Banu, Marimuthu; Shanthi, R. Vijaya; Sivasanker, S. (Results in Engineering, 2022)
<ul class="issue-navigation u-margin-s-bottom u-bg-grey1" id="issue-navigation" style="box-sizing: border-box; margin-top: 0px; margin-right: 0px; margin-left: 0px; padding-right: 0px; padding-left: 0px; list-style: none; overflow: hidden; font-size: 16px; line-height: 24px; color: rgb(46, 46, 46); font-family: NexusSans, Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; margin-bottom: 16px !important; background-color: rgb(245, 245, 245) !important;"> <div class="Abstracts u-font-gulliver text-s" id="abstracts" style="box-sizing: border-box; margin: 0px; padding: 0px; --sd-ui-line-height: calc(1em + 10px); font-size: 0.8rem; line-height: var(--sd-ui-line-height); color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif !important;"> In this article, the results of sorbitol <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/hydrogenolysis" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about hydrogenolysis from ScienceDirect's AI-generated Topic Pages">hydrogenolysis (15% aq. solution), done in an autoclave reactor, over Ru, Pt and Ni loaded on SBA15, carbon coated SBA15 (SBA15C), activated carbon (AcC), Na–Y, Fly Ash (FA) and hydroxyapatite (HAP) catalysts by our group, were compared to find the best metal-support combinations. The metal loading was 1 wt% for Ru and Pt, 6 wt% for Ni and the catalysts' preparations were carried out by impregnation of respective salts. The catalysts were characterized with nitrogen and hydrogen adsorption measurements and X-ray diffraction. Addition of a base (Calcium hydroxide) to the reactants' mixture increased the overall conversion and selectivities of the glycols, ethylene glycol (EG) and 1,2-propylene glycol (PG). The catalysts’ performance at 60 bar and 220 °C with the presence of base (B), evaluated by the yield of glycols (PG + EG), showed the following order: Ni/Na–Y > Ru/AcC ∼ Ru/SBA15C > Ni/HAP ∼ Ru/SBA15 > Ni/SBA15 > Ru/Na–Y > Ni/FA ∼ Ni/AcC and the yields were 57, 40, 39, 33, 31, 29, 26, 22 and 21 wt%, respectively. Na–Y appeared to be the best support, especially for Ni metal; AcC and SBA15C were good supports for Ru and Pt respectively. <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/reusability" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about Reusability from ScienceDirect's AI-generated Topic Pages">Reusability studies revealed that Ni on HAP was the best catalyst and exhibited only a small deactivation during four runs of loading it.